Communicating nutraceuticals: A multi-stakeholder perspective from a developing nation. Issue 3 (2nd July 2016) - Jain, Varsha; Roy, Subhadip; Damle, Neha; Jagani, Khyati
ABSTRACT: Nutraceuticals, a combination of nutrition and pharmaceutical, have grown rapidly as a product globally. Nutraceuticals can be advertised directly to consumers as well as prescribed, and thus involve multiple stakeholders in the marketing communication process. The present study investigates the marketing communication aspects of nutraceuticals using 216 semistructured in-depth interviews including all stakeholders in the process such as company/brand, physicians, pharmacists, and consumers. The findings bring out the role of each participant in the communication process and a comprehensive picture of the same. The insights would facilitate the nutraceutical brands to understand and implement marketing effective communication strategies.